WIRAUSAHA SEBAGAI SOLUSI PENGANGGURAN TERDIDIK DI INDONESIA - Asnawi, Nur (IQTISHODUNA, 2011)
Entrepreneurship is needed by Muslim people. First, it is really reality and objective that aware entrepreneurship is necesssery later. Second, Islamic concept and reality point out the entrepreneurship activity had done by prophet Muhammad SAW and sahabah. It meant Islamic is not only dogmatic but also reality tought in the life. Exhibith Islamic frame is whole of moving life, worship and economic too, inside of entrepneurship. Third, educational institution should support the member to enhance making preparation of the economic training program in growing and improving entrepreneurship spirit at basic level up to high education. And the fourth, as Islamic scholar, muslim should not only effort to apply scientific approach but also emphisize to spritual value quality. As wiseman said “ a effort without praying is arrogant, and praying without trying is nonsence. Spirituality action in reality economic activity meant giving complete value of the profan become unmaterialistic minded and succesful in doing entrepeneurship field, we do hope.